Facial emotion recognition through artificial intelligence - Ballesteros, Jesús A.; Ramírez V., Gabriel M.; Moreira, Fernando; Solano, Andrés; Pelaez, Carlos A. (Frontiers in Computer Science, 2024)
This paper introduces a study using artificial intelligence (A.I.) to employ computer vision algorithms to detect human emotions in video content as users interact with diverse visual stimuli. This research aims to unveil the creation of software capable of emotion detection by identifying users' facial expressions using A.I. algorithms and image processing pipelines. The process involves assessing users through images, enabling the implementation of computer vision algorithms aligned with psychological theories that define emotions and their recognizable features. This study demonstrates the feasibility of emotion recognition through the employed algorithms of convolutional neural networks (CNN) and the software's development and training based on facial expressions. However, to ensure a precise interpretation of emotions, further training is necessary for contexts with more diverse images, alongside additional algorithms that can effectively distinguish between facial expressions depicting closely related emotional patterns, enhancing certainty and accuracy.